2000
DOI: 10.1088/0022-3727/33/19/313
|View full text |Cite
|
Sign up to set email alerts
|

Current and light waveforms associated with the dark- to glow-discharge transition in medium- and low-pressure point-to-plane gaps

Abstract: In nitrogen, for pressures below 200 Torr, the anodic glow is characterized by current oscillations, superimposed on a dc component. These oscillations may be attributed to fluctuations of the space charge, structured as a double sign sheath (double layer). The transition from a dark to a glow discharge can occur either directly from the oscillating state or, in the 20-200 Torr pressure range, through the appearance of a particular regime characterized by recurrent impulses. Both cases are considered here in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 12 publications
6
30
0
Order By: Relevance
“…If the frequency of the applied voltage does not permit this relaxation, the discharge starts on a non-virgin gap with a non-neutral electrical background. All these results are coherent with experimental observations concerning the dark to glow discharges transition in medium and low pressure point-to-plane gaps, which has led also to the hypothesis of a DL formation [14,15].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…If the frequency of the applied voltage does not permit this relaxation, the discharge starts on a non-virgin gap with a non-neutral electrical background. All these results are coherent with experimental observations concerning the dark to glow discharges transition in medium and low pressure point-to-plane gaps, which has led also to the hypothesis of a DL formation [14,15].…”
Section: Discussionsupporting
confidence: 89%
“…The electric field is treated in a quasi-two-dimensional form by the classical 'disks' method [42]. This method implies an assumption on the radial profile of the discharge that, in our case, may be represented by a truncated cone [14,18,20], as has been already mentioned. The radii used in the present study are r c = 0.3 cm on the cathode side and r a = ρ = 0.05 cm on the anode side (ρ being the anode curvature radius).…”
Section: Initial Conditions and Numerical Techniquementioning
confidence: 98%
See 1 more Smart Citation
“…For higher voltages (1300 and 1500 V) passed charge monotonously increases, as expected. Note that after several minutes of poling, the light emission disappears, i.e., the discharge changes its type to the so-called “dark discharge” [ 29 ], though the current remains gradually decreasing. The fact that the poling carries on means that there is still plenty of hydrogen/hydronium ions in the environment of the specimen at this stage.…”
Section: Resultsmentioning
confidence: 99%
“…This quenching time is close to that of DBD, e.g., 50 ns as reported by Gibalov and Pietsch, 16) 20 ns by Braun et al, 17) and 20 ns from light emitted from discharge plasma reported by Dong et al 18) In general, the streamer corona propagates with a velocity of 10 5 -10 6 m/s. [19][20][21][22] The streamer corona propagation time can be estimated to be 1 to 2 ns under our experimental conditions. After the streamer corona bridges between the electrodes, the ''cathode sheath'' is established within 1 to 5 ns.…”
Section: Self-quenching Behaviormentioning
confidence: 85%